2013
DOI: 10.1002/jpln.201100393
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen metabolism is related to improved water‐use efficiency of nodulated alfalfa grown with sewage sludge under drought

Abstract: Leguminous plants grown in sewage sludge–amended soils can acquire nitrogen by assimilation of nitrate and ammonium from the soil solution or from atmospheric‐dinitrogen (N2) fixation through association with N2‐fixing bacteria. We proposed that operation of both metabolic processes could contribute to alleviate the impact of drought in sludge‐treated plants. A greenhouse experiment was conducted to evaluate the involvement of nodule metabolism in the use efficiency of water and N in sludge‐treated plants. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…This is in accordance with lower evapotranspiration and is likely related to less available N and therefore less need of water for biomass growth. Biosolids application increased evapotranspiration (less drainage) compared with the control treatment, which is consistent with the findings of (Fiasconaro et al, 2013), who showed an increased evapotranspiration of leguminous plants after sewage sludge treatment. Using sawdust in combination with biosolids had no benefit with regard to plant growth and evapotranspiration in sorghum.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with lower evapotranspiration and is likely related to less available N and therefore less need of water for biomass growth. Biosolids application increased evapotranspiration (less drainage) compared with the control treatment, which is consistent with the findings of (Fiasconaro et al, 2013), who showed an increased evapotranspiration of leguminous plants after sewage sludge treatment. Using sawdust in combination with biosolids had no benefit with regard to plant growth and evapotranspiration in sorghum.…”
Section: Discussionsupporting
confidence: 91%
“…Through sludge-treatment improved soil moisture unlike the control pots and those treated with mineral fertilizer, water restoration for plants amended by the biosolid was higher, and that all three doses of sludge improve the water content of cells and maintain a higher turgor than the control and that of urea. Similarly, several studies confirm that the organic matter of sewage sludge contributes in the improvement of physical properties of the soil by increasing its water-holding capacity (Singh and Agrawal, 2007[ 56 ]; Fiasconaro et al, 2013[ 19 ]).…”
Section: Discussionmentioning
confidence: 96%
“…Lower NRada key enzyme in the metabolic pathway of Ndin N-deficient plants, however, indicated a lower physiological availability of N in leaves for photosynthesis. Reduced NRa in the leaves is associated with lower availability of N to leaves in cases of N deficiency in various plant species (Reis et al, 2009;Lavres Junior et al, 2010;Fiasconaro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%